Real effects of financial market integration: Evidence from an ECB collateral framework change - Pia Hüttl; Matthias Kaldorf (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
This paper studies the effects of harmonizing collateral policy in a monetary union. In 2007, the European Central Bank replaced national collateral lists with a single list specifying which assets euro area banks can pledge as collateral. Banks holding newly eligible assets experience a reduction in their cost of funding and increase loan supply compared to banks without such assets. The effect is driven by core banks increasing credit supply to riskier and less productive firms located in periphery countries. These firms in turn experience growth in employment and investment. Our results suggest that a harmonized collateral framework facilitates cross-border lending to borrowing-constrained firms and, thereby, increases financial market integration in a monetary union.
Keywords: E44; E52; E58; G20; G21; 330; Collateral Policy; Bank Lending Channel; Financial Integration; Banking Union; Real Effects